2012
DOI: 10.1007/s12070-012-0478-9
|View full text |Cite
|
Sign up to set email alerts
|

Extended High Frequency Audiometry in Secretory Otitis Media

Abstract: The objective of the present study was to determine the status of extended high frequencies in subjects with secretory otitis media. The study evaluated 30 ears of 20 subjects with secretory otitis media in the age group of 15-30 years. This data was compared with 20 ears of 10 volunteers of the same age group with clinically normal hearing. Pure tone air conduction thresholds were analyzed in three frequency groups: low frequency (LF: 0.25, 0.5, and 1 kHz), high frequency (HF: 2, 4, and 8 kHz) and extended hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…However, at low (250–2000 Hz) and high (4000–8000 Hz) frequencies, there was no significant difference between the hearing thresholds of the PCOS group and the control group. Our findings support other studies that also reported findings suggesting that EH frequencies which represent the basal end of the cochlea are often influenced sooner in disorders that cause endothelial and vascular damage [17,20,21]. In one other study, it was reported that chronic inflammation in PCOS could induce of hearing loss, particularly at EH frequencies [11].…”
Section: Discussionsupporting
confidence: 92%
“…However, at low (250–2000 Hz) and high (4000–8000 Hz) frequencies, there was no significant difference between the hearing thresholds of the PCOS group and the control group. Our findings support other studies that also reported findings suggesting that EH frequencies which represent the basal end of the cochlea are often influenced sooner in disorders that cause endothelial and vascular damage [17,20,21]. In one other study, it was reported that chronic inflammation in PCOS could induce of hearing loss, particularly at EH frequencies [11].…”
Section: Discussionsupporting
confidence: 92%
“…All of our histopathologic findings of cochlear and vestibular pathology in human temporal bones are supported by clinical studies of patients with otitis media. High-frequency sensorineural hearing loss secondary to COM has long been demonstrated (Costa et al, 2009; Paparella et al, 1984; Papp et al, 2003); more recent studies have shown sensorineural hearing loss, in regular or extended high frequencies, even in the earlier stages of otitis media, such as SOM and SPOM (Löppönen et al, 1992; Margolis et al, 2000; Sharma et al, 2012). In addition, it has been observed that patients who had SOM in childhood had a higher incidence of tinnitus in adulthood, as compared with control patients who did not have otitis media in childhood (Johnston et al, 2004; Mills and Cherry, 1984; van Cauwenberge et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic and physiologic knowledge of the auditory mechanism reveals that the frequency coding along the basilar membrane progresses from high to low frequencies with the distance from the basal end of the cochlea [ 15 ]. Taken together, these findings indicate that long-term listening to recorded music at high volume may result in harm to the high-frequency basal end of the cochlea, evident here as worse extended high-frequency hearing.…”
Section: Discussionmentioning
confidence: 99%